PPDM PENGOPTIMALISASI POTENSI RUMPUT LAUT DI KECAMATAN KEERA KABUPATEN WAJO, SULAWESI SELATAN - Lendri, Lendri; Husniati, Husniati; Erna, Erna (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2019)
The Development Program of Village (PPDM) is an activity funded by the Ministry of Educationand Technology's 2018 budget year, which aims to improve the economy of the communitythrough superior programs that have been agreed upon. The problems faced by the Keeragovernment in the field of fisheries are: (1). Mining and seaweed business are still virtually freeand have not fully implemented modern technology, (2). The position is that the producer of thecommodity whose tendencies are lower and has less engineering than the outside product, so thatthere is no ability to absorb energy and consumers, (4). The farm products produced generallyhave not yet fulfilled the quality, (5). The market of producers is still a long stretch of consumerand non-transparency, which is the difference between prices of very large prices which arereceived by farms / producers with prices that are paid mainly for products of a Muslim nature, (6).Increased levels of disturbance of organisms in farms and culture and seaweed, (7). Not yet the useof waste from the roots and seaweed, and (7). Not yet related to both the fish and the world ofbusiness. The method of executing the start with the activities of the Socialization of the PPDMProgram in the meetings of the Keera Village which was attended by partners, the government ofKeera District represented by the Secretary of the Sub-District, The head of Keera village, thevillage facilitator and fishermen. The socialization objectives are (1) Explain what will be done bythe PPDM team as well as the error in terms of increasing production partners, (2) Inventory theanalysis that will be given to the owner of the needs. The first year provides training andsupporting equipment production partners, conducts training in other fields; Training of seaweedmanufacture, grass grazing, seaweed screw, lawn juice, and sea grass grass while the equipmentwe provide partners to support production activities namely, spinner, freezer, gas stove, printercake, mixer, display etc., each of these equipment.